Mathematical Modeling and Dynamic Simulation of the Nerinjipettai Hydropower Plant Using MATLAB/Simulink - Kumar, D. Santhosh; Sujatha, V. (Engineering, Technology & Applied Science Research, 2026)
Micro-hydroelectric power is a reliable and efficient source of clean and renewable energy. It can be a fully sustainable method for generating renewable energy from small rivers and streams. The micro-hydro project is designed as a run-of-river system with only a tiny reservoir to operate the turbine, and the water returns to the stream for other purposes without causing significant ecological impact. In this study, a comprehensive MATLAB/Simulink model was developed for the Nerinjipettai Hydropower Plant, incorporating the hydraulic turbine, governor, synchronous generator, and excitation system. A three-phase-to-ground fault was simulated at the generator terminals, where the results showed a terminal voltage dip of about 10% with recovery in 0.6 s, a rotor speed deviation of around 2% that settled within 1.5 s, and mechanical power restored without steady-state error. The novelty of this work lies in integrating plant-specific features of Nerinjipettai with detailed transient fault analysis, which is rarely addressed in previous hydropower modeling studies. The proposed model demonstrates reliable dynamic performance, with the governor and excitation system ensuring system stability. These findings can be applied to optimize control strategies and enhance the efficiency and stability of real-world hydroelectric plants.